General Thoracic and Cardiovascular Surgery Cases - Shiono, Satoshi; Shiose, Akira; Okada, Yoshinori; SpringerLink (Online service) (London : BioMed Central : Imprint: BioMed Central.)
General Thoracic and Cardiovascular Surgery Cases is an official/affiliated journal of the Japanese Association for Thoracic Surgery, the Japanese Association for Chest Surgery, the Japanese Society for Cardiovascular Surgery and the Japan Esophageal Society. This open access, peer-reviewed, online journal will consider any original case reports in the fields of thoracic and cardiovascular surgery. The purpose of the journal is to contribute to the progress of thoracic and cardiovascular surgery by providing clinicians and researchers in the fields with an educational forum in which to disseminate their personal experience and novel treatments to a wide readership and by reviewing interesting, rare cases encountered by colleagues all over the world. .
Keywords: Surgery; Heart$1 (BSurgery.s; Surgery; Cardiac Surgery